PENINGKATAN KETERAMPILAN MEMBACA PEMAHAMAN DENGAN MODEL COOPERATIVE LEARNING TIPE MAKE A MATCH DALAM PEMBELAJARAN BAHASA INDONESIA SISWA KELAS IV DI SDN GONDANGDIA 01 - Nur Azizah, Syafira; Paulus Mbette Suhendro, Petrus; Wartussa'idah, Indah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was conducted to improve the reading comprehension skills of fourthgrade students through the application of the Make a Match Cooperative Learning model in Indonesian language instruction at SDN Gondangdia 01. The study was motivated by students’ difficulties in understanding reading texts, particularly in identifying implicit meanings and evaluating the content critically. This research employed a classroom action research (CAR) approach conducted in two cycles, consisting of planning, implementation, observation, and reflection stages. The participants were 31 students. Data were collected through observation, tests, interviews, and documentation, and analyzed using descriptive quantitative and qualitative methods. The findings revealed an improvement in students’ reading comprehension skills across the cycles. The percentage of learning mastery increased from 74.19% in Cycle I to 93.55% in Cycle II. In addition, both teacher and student activities improved, indicating a more active and engaging learning process. In conclusion, the Make a Match Cooperative Learning model can serve as an effective instructional alternative to enhance reading comprehension skills among elementary school students.